Triterpenes from Shorea negrosensis - Ragasa, Consolacion Y. (Animo Repository, 2014)
Chemical investigations of the dichloromethane extracts of Shorea negrosensis (Foxw.) led to the isolation of friedelin (1), 3β-friedelinol (2), oleanolic acid (3), ursolic acid (4), squalene (5) and chlorophyll a (6) from the leaves, while the twigs yielded 1, 3 and 4. The structures of 1-6 were identified by comparison of their 1H and/or 13C NMR data with those reported in the literature.